Integrative proteomic profiling of lung tissues and blood in acute respiratory distress syndrome - Gong, Rui; Luo, Hong; Long, Gangyu; Xu, Jiqian; Huang, Chaolin; Zhou, Xin; Shang, You; Zhang, Dingyu (Frontiers in Immunology, 2023)
Acute respiratory distress syndrome and acute lung injury (ARDS/ALI) still lack a recognized diagnostic test and pharmacologic treatments that target the underlying pathology. To explore the sensitive non-invasive biomarkers associated with pathological changes in the lung, we performed a integrative proteomic analysis of lung and blood samples from lipopolysaccharide (LPS)-induced ARDS mice and COVID-19-related ARDS patients. The most common differentially expressed proteins (DEPs) were identified based on the ALI model induced by intratracheal LPS instillation. The clinical value of the common DEPs was validated in lung and plasma proteomics in cases of COVID-19-related ARDS. We identified 368 DEPs in serum and 504 in lung samples from LPS-induced ARDS mice. Gene ontology (GO) classification and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that these DEPs in lung tissues were primarily enriched in pathways, including IL-17 and B cell receptor signaling pathways, and the response to stimuli. In contrast, DEPs in the serum were mostly involved in metabolic pathways and cellular processes. Through network analysis of protein-protein interactions (PPI), we identified diverse clusters of DEPs in the lung and serum samples. We further identified 50 commonly upregulated and 10 commonly downregulated DEPs in the lung and serum samples. Internal validation with a parallel-reacted monitor (PRM) and external validation in the Gene Expression Omnibus (GEO) datasets further showed these confirmed DEPs. We then validated these proteins in the proteomics of patients with ARDS and identified nine proteins (C1QC, CD14, HP, LTA4H, PLTP, S100A9, SAA1, SAA2, and SERPINA3) with good clinical prognostic value. These proteins can be viewed as sensitive and non-invasive biomarkers associated with lung pathological changes in the blood and could potentially serve as targets for the early detection and treatment of ARDS.